A pilot study: vital methodological issues - Hazzi, Osama; Maldaon, Issa (Business: Theory and Practice, 2015)
A pilot study represents a vital step for conducting a full-fledged study soundly. In fact, a well-conducted pilot study can help the researchers to design a clear road map they can follow. Conducting a pilot study professionally, however, involves vital quantitative methodological issues (i.e., Back-Translation, Missing Data, Normality, and Reliability) the researchers had better take into account when conducting the pilot study and before embarking the main one. Unfortunately, such issues are neglected in many researches as well as barely addressed together in a one work in research papers. From the literature and the experience, the present work aims to address the most recommended practices of such methodological issues providing at the same time the best practices for new researchers and scholars alike, with a view to reduce the loss of suffered by research community when such issues and practices remain unpublished together. Suggestions and thoughts were also demonstrated in this work for further researches. Finally, the importance of such research for business sector was also demonstrated in this work.